Impact of Sustainability and Business Excellence on Profit Maximization and Customer Centricity: A Study of Multinational Enterprises in APAC - Sharma, Anju (Digital Repository of Theses - SSBM Geneva, 2025)
This study investigates the impact of sustainability and business excellence on profit maximization and customer centricity within multinational enterprises (MNEs) operating in the Asia-Pacific (APAC) region. As global markets evolve, the dual pursuit of economic performance and stakeholder value has gained prominence, particularly in rapidly developing APAC economies. This research explores how sustainability initiatives such as environmental stewardship, social responsibility, and ethical governance, alongside frameworks of business excellence, contribute to enhanced financial performance and deeper customer engagement. Utilizing a mixed-methods approach, the study analyzes data from selected MNEs across key APAC markets to identify patterns, challenges, and strategic outcomes. Findings suggest that organizations integrating sustainability with business excellence frameworks not only achieve higher profitability but also foster long-term customer loyalty and brand equity. The study provides actionable insights for policymakers and corporate leaders aiming to align purpose-driven strategies with financial and customer-focused goals in an increasingly competitive and conscious global marketplace.